Panmen Ready To Die For Williams Bay Land - Nero, Sean (Newsday)
Members of Pan Trinbago's central executive at a media conference said "the steelband fraternity was prepared to die" for the parcel of land at Williams Bay, Chaguaramas, for the purpose of building its headquarters. The response was prompted by a media release issued by the Ministry of Culture with respect to validity of the Steelband body’s claim to ownership.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Pan Trinbago (Organization) -- Headquarters; Land tenure -- Trinidad and Tobago